Chemical principles - Zumdahl, Steven S.
Develop the qualitative, conceptual foundation you need to think like a chemist with CHEMICAL PRINCIPLES, 7e. Designed for students with solid mathematical preparation, this best-seller offers a unique organization that emphasizes models, everyday applications of chemistry, and a thoughtful, step-by-step problem-solving approach